The intersection of TREX1, cGAS, STING and the DNA damage theory of aging - Jones, Kate M.; Chauvin, Samuel D.; Miner, Jonathan J. (Frontiers in Aging, 2025)
Genetic syndromes of immune dysregulation have opened a door toward understanding mechanisms linking inflammation, premature aging, and normal aging. Here, we discuss new insights into the relationship between DNA damage, premature senescence, and nucleic acid-sensing pathways that detect or regulate DNA damage. First, we review mechanisms by which the DNA exonuclease TREX1 negatively regulates the cytosolic DNA sensor cGAS and its downstream effector STING, and we propose a model of TREX1-mediated DNA damage and cellular senescence that implicates age-related, inducible TREX1 expression in the context of genetic disease and inflamm-aging. Our central thesis is that two TREX1-associated diseases—Aicardi-Goutières syndrome (AGS) and retinal vasculopathy with cerebral leukoencephalopathy (RVCL or RVCL-S), historically regarded as inflammatory conditions—can serve as models for research into mechanisms of premature aging.